500 French verbs for dummies - Erotopoulos, Zoe (For dummies, 2013)
The ultimate guide to learning and conjugating verbs in the French language. Complete with English translations, pronunciation guides, and examples of common verb use in everyday conversations, this is an essential reference tool for French language learners of any skill level.